2021
DOI: 10.1038/s41598-021-93567-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus firmus I-1582 promotes plant growth and impairs infection and development of the cyst nematode Heterodera schachtii over two generations

Abstract: Plant-parasitic nematodes wreak havoc on crops by root parasitism worldwide. An approach to combat nematode root parasitism is the application of antagonistic microbes like the rhizobacterium Bacillus firmus I-1582 which is promoted as biological control agent. Although B. firmus is a known nematode antagonist in general, the underlying mechanisms about its interaction with nematodes and plants have not yet been elucidated. Therefore, we explored the influence of B. firmus I-1582 as well as its extracellular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 67 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…Arbuscular mycorrhizal fungi efficiently colonize roots of Cymbopogon citratus and induce the activity of defense-related enzymes, such as peroxidase, β-1,3-glucanase, and polyphenol oxidase, thus suppressing root lesion nematode infection ( Silva et al, 2021 ). Arabidopsis thaliana root colonization by B. firmus I-1582 significantly inhibits the infection and reproduction of the beet cyst nematode Heterodera schachtii ( Huang et al, 2021 ). In our study, the Bv-25 was obtained from the rhizosphere of cucumber and so easily colonized cucumber roots.…”
Section: Discussionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi efficiently colonize roots of Cymbopogon citratus and induce the activity of defense-related enzymes, such as peroxidase, β-1,3-glucanase, and polyphenol oxidase, thus suppressing root lesion nematode infection ( Silva et al, 2021 ). Arabidopsis thaliana root colonization by B. firmus I-1582 significantly inhibits the infection and reproduction of the beet cyst nematode Heterodera schachtii ( Huang et al, 2021 ). In our study, the Bv-25 was obtained from the rhizosphere of cucumber and so easily colonized cucumber roots.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in addition to promoting plant growth, Bacillus amyloliquefaciens FZB42 is also able to produce a large number of secondary metabolites that are non-ribosomal [ 24 ]. Bacillus cereus may potentially be used as a plant-growth-promoting bacterium [ 25 ], with the potential to synthesize plant-growth hormones [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, not all microbial BCAs have suppressive effects on nematodes. Many bacteria and fungi (some of which are endophytes), including arbuscular mycorrhizal fungi (AMF), have plant-promoting effects instead and can induce plant defense mechanisms against PPNs, namely, by managing phytohormone levels, inducing signal substrate production, regulating gene expression, and enhancing protein production, and they have been extensively used as plant health promoters and BCAs against harmful nematodes [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Bacterial mechanisms to antagonize PPNs may include the production of antibiotics, endospores, hydrolytic enzymes, volatile organic compounds (VOCs), Cry proteins (pore-forming toxins), and Trojan horses, which lure nematodes by emitting VOCs and secreting proteases or toxins upon entry into their host, ultimately killing the nematode [ 17 , 38 , 39 , 40 ] ( Figure 2 ).…”
Section: Microbes Against Plant-parasitic Nematodesmentioning
confidence: 99%
“…From 2018 to 2022, the most commonly studied bacterial agents against cyst nematodes belong to the Bacillus genus. Huang et al [ 30 ] explored the effects of B. firmus I-1582 on the plant–nematode interaction between A. thaliana and H. schachtii and found that the root colonization by the rhizobacterium significantly protected A. thaliana from infestation by the BCN, negatively affecting nematode reproduction as well as pathogenicity and development over two generations in vitro [ 30 ]. Widianto et al [ 66 ] evaluated the pathogenicity of B. cereus , B. flexus , B. megaterium , B. pumilus , and B. subtilis on G. rostochiensis , and noticed significantly contrasting protease and chitinase activities in these strains compared to the control.…”
Section: Microbes Against Plant-parasitic Nematodesmentioning
confidence: 99%